Enamel Microstructure in Eocene Cetaceans from Antarctica (Archaeoceti and Mysticeti) - Loch, Carolina; Buono, Mónica Romina; Kalthoff, Daniela C.; Mörs, Thomas; Fernández, Marta Susana (Journal of Mammalian Evolution)
Modern baleen whales have no adult teeth, whereas dolphins and porpoises have a homodont and polydont dentition, with simplified enamel microstructure. However, archaic cetaceans (archaeocetes and early mysticetes and odontocetes) had a complex and ornamented dentition, with complex enamel microstructure as in terrestrial mammals. This study describes the morphology of teeth and enamel microstructure in two fossil cetaceans from Antarctica: a basilosaurid archaeocete from the La Meseta Formation (middle Eocene); and Llanocetus sp. from the Submeseta Formation (late Eocene), one of the oldest mysticetes known. The two teeth analyzed were lower premolars, with transversely compressed triangular crowns composed of a main cusp and accessory denticles. The enamel microstructure of the basilosaurid and Llanocetus sp. is prismatic with Hunter-Schreger bands (HSB) and an outer zone of radial enamel. In the basilosaurid, the enamel is relatively thin and measures 150–180 μm, whereas in Llanocetus sp. it is considerably thicker, measuring 830–890 μm in the cusp area and 350–380 μm near the crown base. This is one of the thickest enamel layers among cetaceans, extinct and living. Structures resembling enamel tufts and lamellae were observed in both fossils at the enamel-dentine junction (EDJ) and extending along the thickness of the enamel layer, respectively. The presence of HSB and biomechanical reinforcing structures such as tufts and lamellae suggests prominent occlusal loads during feeding, consistent with raptorial feeding habits. Despite the simplification or absence of teeth in modern cetaceans, their ancestors had complex posterior teeth typical of most mammals, with a moderately thick enamel layer with prominent HSB. Fil: Loch, Carolina. University of Otago; Nueva Zelanda Fil: Buono, Mónica Romina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Instituto Patagónico de Geología y Paleontología; Argentina Fil: Kalthoff, Daniela ...